ImageJ-FIJI-Assisted Estimation of Intestinal Layers' Volume: Study in Jejunum-Ileum of Rats - Wicaksono, Satrio Adi; Sumiwi, Yustina Andwi Ari; Paramita, Dewi Kartikawati; Susilowati, Rina (The journal of microscopy & ultrastructure, 2024)
Abstract Background: Studies in the digestive tract often required precision quantification of intestinal volume to observe the effect of certain intervention/condition. Application of stereological methods could bring unbiased and accurate results but commercially computer-assisted systems are not widely available. ImageJ-FIJI is an open source software, which could become an alternative choice in the stereological measurement process. Aim: This study describes simple stereological quantification methods during volume estimation of jejunum-ileum intestinal layers of the rats using a light microscope and ImageJ-FIJI stereological tool. Material and Methods: Six 3-months old male Sprague-Dawley rats were terminated and jejunum-ileum was harvested after perfusion. After removal of intestinal luminal content, whole jejunum-ileum weight was measured. The organ was sampled as 6-10 slabs of 1 cm length in a systematic uniformed random sampling manner. Slabs were cut longitudinally at random angles before flattened and put on filter papers for subsequent tissue processing into 2-3 paraffin blocks. One section of 3 μm thick was sampled from each block, stained using toluidine blue and documented using a light microscope connected to a microstepper apparatus. The volume of the intestinal layers was estimated using a point-counting grid on Image J-FIJI software. Result: We compared two sets of counting methods i.e. minimal counting (MC) and rigorous counting (RC) approaches that differ in their respective a/p value. Quantification using RC approach resulted in significantly higher estimated volume of tunica submucosa and tunica muscularis while having more preferable stereological accuracy parameters (CE<5% & CV<10%). Conclusion: Although it required longer counting time, rigorous approaches resulted in higher accuracy while still within the range of rule of thumb criteria of 0.2 < CE2/CV2 < 0.5.